Conceptualizing ‘Country-of-Ingredient-Authenticity’ for Luxury Brands - Zainol, Siti Nurzahirah Zakiah Binti (Curtin University, 2015)
The study investigates the influence of “consumers’ need for ingredient authenticity” towards product and brand evaluations and purchase intentions of luxury brands. A scale to measure ‘consumer needs for ingredient authenticity’ and a new construct ‘country-of-ingredient-authenticity’ were developed. The methodology entails a 3X2X2 factorial experimental design to examine the effects of three luxury brands from two levels of country image (high vs low) and two authenticity cues (raw materials vs artisan skills).